2019
DOI: 10.7819/rbgn.v21i5.4025
|View full text |Cite
|
Sign up to set email alerts
|

How Social Support Motivates Trust and Purchase Intentions in Mobile Social Commerce

Abstract: Purpose-This study refers to the social support and trust theories to explore what kind of factors affect the users' intention to adopt MSC. Design/methodology/approach-A total of 207 subjects who had previously experienced or known about MSC were identified and partial least squares were performed to analyse the measurement and structural models. Findings-The results indicated that MSC purchase intentions are affected significantly by four other factors (social support, perceived usefulness, subjective norm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 82 publications
(102 reference statements)
5
32
0
Order By: Relevance
“…For example, Chen et al [28] proved that impulsive buys are controlled by the emotional trust of the recommender and empathy towards the proposed product in the WeChat app. Similarly, Liu et al [18] proved that perceived usefulness, trust, subjective norm and social support do have an effect on MSC purchase intention.…”
Section: Mobile Social Commerce Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, Chen et al [28] proved that impulsive buys are controlled by the emotional trust of the recommender and empathy towards the proposed product in the WeChat app. Similarly, Liu et al [18] proved that perceived usefulness, trust, subjective norm and social support do have an effect on MSC purchase intention.…”
Section: Mobile Social Commerce Literature Reviewmentioning
confidence: 92%
“…This impact has been confirmed by several empirical studies in ICT since peers', family members' and friends' points of view exert a positive impact on users' behavior. In the context of MSC, Liu et al [18] and Zhang and Wang [45] proved its effect on adoption intention. Furthermore, various studies also confirmed the effect of social influence on performance expectancy.…”
Section: Social Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, trust can be considered as a major prerequisite for S-Commerce success. The empirical study of Liu et al (2019) has affirmed that trust is a major predictor of customers' decisions in shopping through S-Commerce. Therefore, the following hypothesis is formulated:…”
Section: Shirkah: Journal Of Economics and Businessmentioning
confidence: 99%
“…Thus, support can trigger positive action among individuals (Turner & Brown, 2010). According to past studies, social support can influence behavioral intention in an online shopping platform (Hajli, 2014;Liang et al, 2011;Liu et al, 2019;Makmor et al, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%